2013
DOI: 10.3390/biology2020481
|View full text |Cite
|
Sign up to set email alerts
|

Nonindigenous Plant Advantage in Native and Exotic Australian Grasses under Experimental Drought, Warming, and Atmospheric CO2 Enrichment

Abstract: A general prediction of ecological theory is that climate change will favor invasive nonindigenous plant species (NIPS) over native species. However, the relative fitness advantage enjoyed by NIPS is often affected by resource limitation and potentially by extreme climatic events such as drought. Genetic constraints may also limit the ability of NIPS to adapt to changing climatic conditions. In this study, we investigated evidence for potential NIPS advantage under climate change in two sympatric perennial sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 92 publications
1
8
0
Order By: Relevance
“…Most previous studies on the impact of eCO 2 associated with drought and/or elevated temperature did not report whole ecosystem responses, but primarily plant responses at various organizational levels. Generally, they show that eCO 2 alleviates the stress associated with drought and/or elevated temperature (4,16,18,(22)(23)(24)(25)(26)(27)(28), but some studies found inconsistent responses (29)(30)(31)(32)(33)(34)(35)(36). This variability could be linked with the seasonality of precipitation (35,37) or with the intensity and length of the imposed stress, because the effect of eCO 2 has been shown to be positive under moderate drought and negligible under severe stress when stomata are fully closed (14).…”
Section: Resultsmentioning
confidence: 99%
“…Most previous studies on the impact of eCO 2 associated with drought and/or elevated temperature did not report whole ecosystem responses, but primarily plant responses at various organizational levels. Generally, they show that eCO 2 alleviates the stress associated with drought and/or elevated temperature (4,16,18,(22)(23)(24)(25)(26)(27)(28), but some studies found inconsistent responses (29)(30)(31)(32)(33)(34)(35)(36). This variability could be linked with the seasonality of precipitation (35,37) or with the intensity and length of the imposed stress, because the effect of eCO 2 has been shown to be positive under moderate drought and negligible under severe stress when stomata are fully closed (14).…”
Section: Resultsmentioning
confidence: 99%
“…While eco-physiological distinctiveness is certainly a feature of NNGs, many have morphological and ecological similarities to native congeners or analogues (e.g., Godfree et al 2013), and there may be substitutability among grasses that would allow for a basic level of connectivity and resource provision to be maintained, even in invaded landscapes. Perhaps some trade-off species have a smaller impact on conservation value than others, in which case prioritising their use could help retain multi-value landscape elements.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly true when sympatric native species have similar morphological attributes (e.g., Godfree et al 2013), or when the production of floral parts has been affected by drought or overgrazing. For example, it is common for new populations of H. hirta, E. curvula, and especially Nassella spp., which are morphologically similar to Australian native Themeda, Cymbopogon, Poa, and Austrostipa species, to go unrecognised for many years.…”
Section: The Management Challengementioning
confidence: 99%
See 1 more Smart Citation
“…Many invasive and native plants increase biomass production and fecundity under elevated [CO 2 ], a response known as the CO 2 fertilization effect (Godfree et al, 2013). Because trade-offs exist between acquisition of atmospheric CO 2 and water loss, altering [CO 2 ] changes physiological processes taking place in plant tissue, in turn altering plant growth and water use efficiency.…”
Section: Climate Change and Plant Invasionsmentioning
confidence: 99%